Implementation of Flipped Classroom Model in Vocational High School: A Systematic Literature Review - Cobena, Desy Yanty; Surjono, Herman Dwi (JTP - Jurnal Teknologi Pendidikan, 2022)
This research aims to provide a comprehensive overview of flipped classroom implementation in Indonesian Vocational High School (VHS). Articles were searched using Google Scholar and selected using the PRISMA (Preferred Reporting Items for Systematic reviews dan Meta-Analyses) method. Only articles indexed by Sinta (a scientific database designed by the Ministry of Researcher, Technology and Higher Education of The Republic of Indonesia) or Scopus were used. Twenty-nine articles were included, published from 2017 to 2021. The results revealed that flipped classroom in Indonesian VHS impacts students’ interests and motivation. Moreover, it impacts students’ affective, cognitive, and psychomotor competencies and personal skills in the form of self-efficacy, critical thinking, problem-solving, communication, and resilience. Various learning media and tools can be integrated into out-of-class and in-class activities, embodied in learning design. As the topic of future research, the authors recommended investigating the impact of the flipped classroom on other research areas, integrating flipped classroom with other learning models and evaluating the effectiveness, also developing learning media to improve the learning outcomes.